Optimizing Employee Performance: The Impact of Placement and Standard Operating Procedures in Samarinda City Government Agencies - Sabtohadi, Joko; Rahmasita, Azi Nur; Rahmadi, Muhammad Harry; Jubaidi, Jubaidi; Paradila, Anisa; Rin, Anggraita Fuspa; Nendra, Andre Ray; Qomariyah, Anis; Periadi, Anisa Maqwani Retalita Putri (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the impact of Placement and Standard Operating Procedures (SOPs) on employee performance in the Kota Samarinda government agency. Using a quantitative approach, the research analyzed data from 59 respondents through questionnaires to evaluate the significance of these variables. The findings reveal that both Placement and SOPs significantly influence employee performance. Specifically, Placement has a positive effect, as indicated by a significant t-test result (t = 2.800), while SOPs also show a strong positive impact (t = 3.944). The overall F-test (F = 178.681) further confirms that the combined effect of Placement and SOPs significantly affects employee performance. Based on these results, the study recommends enhancing performance evaluations, aligning employee placements with job requirements, and continuously updating SOPs. Additionally, digitalizing SOPs is suggested to ensure transparency and accessibility within the agency.